Targeting PKCθ in alloreactivity and graft-versus-host-disease: unanswered questions and therapeutic potential - Bronk, Crystina; Yu, Xue-Zhong; Beg, Amer (Frontiers in Immunology, 2012)
Protein kinase C isoform theta (PKC theta) is a key modulator of TCR signaling and mediates activation of NF-kappaB, NF-AT and AP-1 transcription factors. Although in vitro studies of PKC theta-/- T cells have shown impaired activation responses, in vivo studies indicate that PKC theta requirement is not universal. While PKC theta is important in induction of experimentally-induced autoimmune diseases in mice and generation of Th2 responses, it is not essential for induction of T cell proliferative and cytotoxic responses against influenza virus, LCMV and vaccinia virus. The context-specific involvement of PKC theta in T cell responses suggests that inhibition of PKC theta may be beneficial in some but not all situations. In the bone marrow transplantation (BMT) setting, we have shown that graft-versus-host-disease (GVHD) cannot be induced in the absence of PKC theta. However, graft-versus-leukemia (GVL) effects and T cell ability to clear virus infection remains intact. Therefore, PKC theta is a potential therapeutic target in BMT, inhibition of which may prevent GVHD while retaining anti-tumor and anti-infection responses.